A Tradeoff between the Output and Current Account Effects of Pension Reform - Catalan, Mario (IMF Working Papers; Working Paper ;, 2012)
We compare the long-term output and current account effects of pension reforms that increase the retirement age with those of reforms that cut pension benefits, conditional on reforms achieving similar fiscal targets. We show the presence of a policy trade-off. Pension reforms that increase the retirement age have a large positive effect on output, but a small (and often negative) effect on the current account. In contrast, reforms that cut pension benefits improve the current account balance but reduce output. Mixed pension reforms, which extend the working life and cut pension benefits, can simultaneously boost output and the current account.